Decarbonizing power systems: A critical review of the role of energy storage. (April 2022) - Jafari, Mehdi; Botterud, Audun; Sakti, Apurba
Abstract: Meeting greenhouse gas (GHG) emissions reduction targets will require a multi-pronged approach to decarbonizing all GHG-contributing sectors, including intersectional strategies across sectors. A deep decarbonization of the power sector is integral to achieving any meaningful target; energy storage systems (ESSs) have emerged as a frontrunner in addressing some of the challenges facing a transition towards renewables-based power supply. Here we document a systems-level review of over 100 relevant studies to underline key takeaways on the role of ESSs and highlight research gaps. We find a) most decarbonization studies investigating the role of ESSs do not consider ambitious emissions targets like the intergovernmental panel on climate change's (IPCC's) goal to keep the global temperature rise below 1.5 °C, b) the role of ESSs in low-carbon electricity pathways rely heavily on local contexts (such as decarbonization policy etc.) c) from a technology perspective, duration and capital cost are the main factors in assessing the viability of each ESS technology; the dominant role for short-duration storage (e.g., batteries) is solar energy integration and partially replacing peaker plants, mid-duration storage (e.g., flow batteries, PHES) contributes to wind energy integration and in decreasing variable renewable energy (VRE) curtailments, while long-duration storage (e.g., CAES, P2G, hydrogen) provides long-term (seasonal) energy shifts, d) virtual ESS solutions can provide similar flexibility without high hardware investment requirements but rather through improved algorithms for optimization, control and measurements, and e) planning models that do not account for the technical characteristics of ESS technologies are inadequate to assess technology tradeoffs. Highlights: Studies often do not account for ambitious decarbonization targets. Decarbonization policies, geography, cost and technology drive storage's role. Storage duration determines planning and operational roles in decarbonization. Virtual storage can play a role through advanced control and optimization. Studies rely on simplistic storage models that can substantially alter results.